Charisma and canon: essays on the religious history of the Indian subcontinent - Dalmia, Vasudha; Malinar, Angelika; Christof-Füchsle, Martin (Oxford Univ. Press, 2001)
Papers presented at a symposium held at Blaubeuren, Germany from May 17-21, 1997
Includes bibliographical references
Keywords: India -- Congresses -- Religion; Konferenzschrift; Aufsatzsammlung; Geschichte; Religion; Indien